HÁBITOS DE ESTUDIO EN EL ÁREA DE MATEMÁTICA DE LOS ESTUDIANTES DE LA UNIDAD EDUCATIVA COMBATIENTES DE TAPI. RIOBAMBA. OCTUBRE 2017-MARZO 2018. - Rosero Vivas, Ketty Tamara (2020)
The purpose of this research project is to determine the study habits in the area of mathematics in the Sixth Year students of Basic General Education of the Educational Unit "Combatientes de Tapi" of the city of Riobamba. Theoretically, the study habits are all the actions that are repeated constantly to get a habit. This study was carried out under descriptive and correlational research. An intentional non-probabilistic sample of 29 students between 10 and 11 years of age corresponding to the Sixth Year of Basic General Education "A" Parallel consists of 19 males and 10 females. The techniques that used for the data collection were the Survey of Habits and Study Techniques (CHTE) that consists of 56 questions where the scores obtained in each of the seven scales. Though the record of qualifications of the Mathematics area, it determined that the study habits have a positive relationship with Mathematics since students have an adequate attitude towards the study of it. To carry out their learnig they take into account the place where they will study, the place is organized clean and has all the materials they will use to carry out their work. Students also plan the time they will need to learn mathematics.